INTEGRATED MARKETING COMMUNICATION VIERA OLEH-OLEH DALAM MEMPERTAHANKAN BRAND AWARENESS - Windy Aulia Asshafa; Ringgo Eldapi Yozani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Viera Souvenirs is a typical Riau Malay souvenir shop located in Pekanbaru City and has been established since 2015. Good business prospects in the field of selling souvenirs typical of Pekanbaru City have certainly caused many similar competitors to emerge. So that makes Viera Souvenirs continue to be aggressive in carrying out marketing communication activities. Viera Souvenirs communicates Viera Souvenir products and stores to the public by carrying out a series of marketing communication activities by applying the concept of Integrated Marketing Communication (IMC). The purpose of this study was to find out the implementation and form of integration of IMC elements carried out by Viera Souvenir in maintaining brand awareness in the people of Pekanbaru. This study uses a qualitative method. This research was conducted at the Viera Souvenir Shop on Jl. Melati No.2, Simpang Baru, Kec. Tampan, Pekanbaru City. The selection of informants was carried out using a purposive technique. Using data collection techniques through observation, interviews, and documentation. Meanwhile, to test the validity of the data, researchers used extended participation and triangulation. The results of this study are in maintaining brand awareness of Viera Souvenirs in the people of Pekanbaru city, Viera Souvenirs uses five elements of IMC namely advertising, sales promotion, personal selling, sponsorship and social media marketing. While the form of integration carried out is the divisional unit in Viera Souvenirs to operate the Viera Souvenirs marketing communication program and other forms of integration are from messages such as logos, images, and product specifications of Viera Souvenirs which are designed in shades of yellow according to the company concept. Overall, the IMC carried out by Viera Souvenir can be said to be quite good. Which is brand Awareness that is maintained in Pekanbaru society today up to the level of brand recognition. Which people can describe the specifications of Viera Souvenirs.